NF‐κB‐inducing kinase is a key regulator of inflammation‐induced and tumour‐associated angiogenesis. Issue 3 (28th August 2014) - Noort, Ae R; van Zoest, Katinka PM; Weijers, Ester M; Koolwijk, Pieter; Maracle, Chrissta X; Novack, Deborah V; Siemerink, Martin J; Schlingemann, Reinier O; Tak, Paul P; Tas, Sander W
Abstract Angiogenesis is essential during development and in pathological conditions such as chronic inflammation and cancer progression. Inhibition of angiogenesis by targeting vascular endothelial growth factor (VEGF) blocks disease progression, but most patients eventually develop resistance which may result from compensatory signalling pathways. In endothelial cells (ECs), expression of the pro‐angiogenic chemokine CXCL12 is regulated by non‐canonical nuclear factor (NF)‐κB signalling. Here, we report that NF‐κB‐inducing kinase (NIK) and subsequent non‐canonical NF‐κB signalling regulate both inflammation‐induced and tumour‐associated angiogenesis. NIK is highly expressed in endothelial cells (ECs) in tumour tissues and inflamed rheumatoid arthritis synovial tissue. Furthermore, non‐canonical NF‐κB signalling in human microvascular ECs significantly enhanced vascular tube formation, which was completely blocked by siRNA targeting NIK. Interestingly, Nik−/− mice exhibited normal angiogenesis during development and unaltered TNFα‐ or VEGF‐induced angiogenic responses, whereas angiogenesis induced by non‐canonical NF‐κB stimuli was significantly reduced. In addition, angiogenesis in experimental arthritis and a murine tumour model was severely impaired in these mice. These studies provide evidence for a role of non‐canonical NF‐κB signalling in pathological angiogenesis, and identify NIK as a potential therapeutic target in chronic inflammatory diseases and tumour neoangiogenesis. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.